Blockchain-based 5G handoff authentication system using joint-graph-based delegated practical byzantine fault tolerance consensus approach - Ravindra Janardan Lawande; Sudhir Bapurao Lande; Shailendrakumar Mahadeo Mukane (Universitas Ahmad Dahlan, 2026)
The 5G mobile networks offer extra benefits in terms of high data rates, lower latency, and more coverage in comparison to 4 G networks. However, the 5G network offers new levels of data transfer and processing speeds, ensuring users do not disconnect as they move from one cell to another. By considering these issues, this paper proposes a new blockchain-based, scalable, and reliable 5G handoff authentication system. The proposed approach is intended to ensure authentication using Exponential Elliptic Curve-Assisted Encryption (EEE) between the user and the base station. After the successful authentication, the user stores the details in the source base station. In a blockchain-based 5G handoff authentication system, when a user device enters the range of a new base station, it sends a handoff request using a pseudorandom frequency-hopping sequence. The serving base station sends a handover command to the mobile device, containing details about the target base station and the next frequency in the hopping sequence. This request is disseminated through an improved gossip algorithm that minimizes communication overhead and accelerates node authentication in the blockchain for consensus and validation. Similarly, in blockchain networks, the gossip protocol ensures that every node in the network receives information about the request for handoff while ensuring that the messages sent are not redundant. Therefore, the joint graph-based Delegated Practical Byzantine Fault Tolerance (JG-DPBFT) consensus process is utilized to verify the handoff.